Factors affecting microbial safety behavior of beef handlers working in major beef retailers in Mizan-Aman, Southwest Ethiopia - Girma Mamo Zegene; Seid Tiku Mereta; Seblework Mekonen (PLoS ONE, 2025)
Background Beef is a key component of human diet but also a favorable medium for microbial growth. However, research has largely overlooked major beef retailers and the specific roles of handlers, missing critical points for intervention. This study aims to address these gaps to support targeted microbial safety measures based on handlers’ specific roles in beef processing. Methods A cross-sectional study was conducted in Mizan-Aman, Southwest Ethiopia, from February 20 to April 20, 2024. The sample size was determined using a single population proportion formula, resulting in the inclusion of 372 participants, yielding a response rate of 360 (96.8%). Beef retailers were randomly selected, while beef handlers were chosen through systematic sampling technique. Data collection was done using a structured questionnaire and observation checklist. Following a quality assessment, the data were analyzed using STATA 16, employing descriptive statistics and logistic regression. Bivariable analysis (p ≤ 0.25) was performed to identify variables for multivariable analysis. Statistical significance was assessed using adjusted odds ratios (AOR) and 95% confidence intervals (CI), with a significance level set at p < 0.05. Results Findings indicated that a significant proportion of beef handlers demonstrated inadequate knowledge (61%), negative attitudes (58%), and insufficient safety practices (55%). Among several factors associated with knowledge, attitude and practice of beef handlers, training in food safety was linked to good knowledge (AOR = 4.17, 95% CI: 1.15–15.12), while the role of a waiter was associated with both good knowledge (AOR = 4.5, 95% CI: 1.83–10.95), and more favorable attitudes (AOR = 2.8, 95% CI: 1.02–7.31). On the other hand, poor knowledge (AOR = 4.40, 95% CI: 2.44–7.94) and unfavorable attitudes (AOR = 4.84, 95% CI: 2.62–8.95) were significantly correlated with inadequate microbial safety practices. Conclusion Many beef handlers lack sufficient knowledge, attitudes, and practices regarding beef safety, regardless of their job roles. Improving microbial safety requires strategies such as formal education, training, health checks, and certification.